Enhancing Sustainable Irrigation Practices through Innovative Maize Technologies: A Study of Sedeni and Golina1 Schemes in North Wollo Zone, Ethiopia - Abate, Sisay Dessale; Mihret, Tewabe; Tilahun, Gebeyaw; Sisay, Kassa; Biyazen, Brihanu; Feyisa, Tesfaye; Yitayew, Asresu; Fenta, Tigabu; Abere, Eyeberu; Getnet, Abera; Adisie, Samuel; Andre, Andre (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Inadequate rainfall with uneven distribution in time and space could harm the rainfed agriculture in the semi-arid regions of Eastern Amhara. Hence, irrigation is crucial to provide crop production and economic benefit. Therefore, the pre-scale-up aimed to promote improved irrigation technologies to increase grain yield, water use efficiency, and net benefit of maize. For comparison, two forms of irrigation practices (traditional and improved) were tested following the Farmer Research Extension Group (FREG) approach. The improved irrigation practices include agronomic packages (200 kg ha-1 Urea and 50 kg ha-1 NPS, seed rate of 25 kg ha-1, the spacing between rows and plants were 75 cm and 30 cm respectively), furrow irrigation (0.15 m furrow height, 0.25 m furrow width, and 0.2% furrow gradient). In Sedeni and Golina1, the net irrigation depths were 11.2 mm and 12.4 mm, 28.4 mm and 30.6 mm, 36.6 mm, and 37.8 mm, and 24.7 mm and 27.4 mm for initial, development, mid, and late stages, respectively. Depending on the agroecological similarities of the two sites, the irrigation was applied in 10-day intervals. The farmer's practice included: a local variety, broadcast sowing with 40 kg ha-1, traditional flooding applied in 12 day intervals, 50 kg ha-1 Urea and NPS each. The quantitative data was recorded by field monitoring and the farmer's perceptions were collected from the FREG members using a semi-structured questionnaire survey. The collected data was analysed by descriptive statistics. The result showed that the maximum marketable green cob yield (38,125 and 34,330 cobs ha−1), water productivity (17 cobs m-3 and 16 cob m-3), and maximum net benefit (222,575.00 ETB ha-1 and 174,487.00 ETB ha-1) for Golina1 and Sedeni respectively was recorded from the improved practices. Whereas farmer's practices gave minimum green yield (29,351 ha−1 and 26,368 ha−1), water productivity (10 cob m-3 and 8 cob m-3), and net benefit (123,905.00 ETB/ha, and 93,390.00 ETB/ha,) for Golina1 and Sedeni, respectively. Therefore, improved irrigation and agronomic practices had 29.9% and 30.2% green cob yield, and 79.63% and 86.84% net benefit advantage for Golina1 and Sedeni, respectively. In these respective small-scale irrigation schemes, the improved practices had lower seasonal net irrigation water demand (230 mm and 219.4 mm) than the farmer's practices (302.4 mm and 351 mm). It implies that the improved practices saved 72.4 mm and 131.6 mm of water for Golina1 and Sedeni respectively over the farmer's practices. Hence, from the result, it could be concluded that improved irrigation management practices (furrow irrigation, irrigation frequency, amount, row planting, plant spacing, seed rate, and recommended fertilizer, and improved seed Melkassa- 6Q) were more efficient in achieving high green cob yield, water productivity, water saving, higher net benefit, and acceptability by the FREG members. Keywords: FREG, scale up, Small-scale irrigation, technologies.